b3galt6 Knock-Out Zebrafish Recapitulate β3GalT6-Deficiency Disorders in Human and Reveal a Trisaccharide Proteoglycan Linkage Region - Delbaere, Sarah; De Clercq, Adelbert; Mizumoto, Shuji; Noborn, Fredrik; Bek, Jan Willem; Alluyn, Lien; Gistelinck, Charlotte; Syx, Delfien; Salmon, Phil L.; Coucke, Paul J.; Larson, Göran; Yamada, Shuhei; et al. (Frontiers in Cell and Developmental Biology, 2020)
Proteoglycans are structurally and functionally diverse biomacromolecules found abundantly on cell membranes and in the extracellular matrix. They consist of a core protein linked to glycosaminoglycan chains via a tetrasaccharide linkage region. Here, we show that CRISPR/Cas9-mediated b3galt6 knock-out zebrafish, lacking galactosyltransferase II, which adds the third sugar in the linkage region, largely recapitulate the phenotypic abnormalities seen in human β3GalT6-deficiency disorders. These comprise craniofacial dysmorphism, generalized skeletal dysplasia, skin involvement and indications for muscle hypotonia. Disturbed collagen fibril organization was the most consistent ultrastructural characteristic throughout affected tissues. Strikingly, despite a strong reduction in glycosaminoglycan content, we identified a small amount of proteoglycans containing a unique linkage region consisting of only three sugars. This implies that formation of glycosaminoglycans with an immature linkage region is possible in a pathogenic context. Our study therefore unveils a novel rescue mechanism for β3GalT6-deficiency, opening new avenues for therapeutic intervention.